Scaled Down Modelling of a Horizontal Wind Turbine for a Floating Wind Turbine Research - Erol, Serkan; Özkol, Ünver (Izmir Institute of Technology, 2020)
Floating wind turbines have to operate under the influence of hydrodynamic and aerodynamic forces which are usually coupled in nature. Due to complicated interactions of wave and wind forces on its structure, predicting motion and performance of a floating wind turbine usually depend on many assumptions. In order to understand the dynamics of the system, experimental studies are required to obtain results by taking into account all parameters. This study is a part of a Tübitak project (217M451) that investigates the dynamics of different floating platforms with a wind turbine attached to it under an atmospheric boundary layer wind profile. In this thesis, a scaling methodology was used to model a wind turbine to use in experimental studies. Reynolds number discrepancy was demonstrated in floating wind turbine modeling. For this reason, the method was created by using Froude number and tip speed ratio similitude, and geometric, kinematic and dynamic similarity was achieved. According to the created methodology, an onshore wind turbine that has 320kW nominal power was scaled down to be used in experimental studies according to the open sea conditions. Along with the model turbine, a thrust force measuring mechanism, hot-wire sensor travers system and a motion detection method by a video have been realized. A wave maker and a wind nozzle which are the part of the Tübitak project of which the model turbine described in this thesis will be used, therefore; small description of those are also given in the thesis.

Yüzer rüzgar türbinleri genellikle doğada birleşmiş hidrodinamik ve aerodinamik kuvvetlerin etkisi altında çalışmak zorundadır. Dalga ve rüzgar kuvvetlerinin yapısı üzerindeki karmaşık etkileşimleri nedeniyle, yüzen bir rüzgar türbininin hareket ve performansının tahmin edilmesi genellikle birçok varsayıma bağlıdır. Sistemin dinamiklerini anlamak için tüm parametreler dikkate alınarak sonuçların elde edilmesi için deneysel çalışmaların yapılması gerekmektedir. Bu çalışma, bir atmosferik sınır tabaka rüzgar profili altında kendisine bağlı bir rüzgar türbini ile farklı yüzen platformların dinamiklerini araştıran Tübitak projesinin (217M451) bir parçasıdır. Bu tezde, bir rüzgar türbinini modellemek ve deneysel çalışmalarda kullanmak için bir ölçekleme metodolojisi kullanılmıştır. Reynolds sayısı tutarsızlığı, yüzer rüzgar türbini modellemesinde gösterilmiştir. Bu nedenle yöntem Froude sayısı ve kanat uç hızı oranı benzerliği kullanılarak oluşturulmuş, geometrik, kinematik ve dinamik benzerlik sağlanmıştır. Oluşturulan metodolojiye göre, 320kW nominal güce sahip bir kara rüzgar türbini açık deniz koşullarına göre deneysel çalışmalarda kullanılmak üzere ölçeklendirilmiştir. Model türbin ile birlikte bir itme kuvveti ölçüm mekanizması, sıcak-tel sensörü için travers sistemi ve bir video ile hareket algılama yöntemi gerçekleştirilmiştir. Tübitak projesinin bir parçası olan ve bu tezde tarif edilen model türbinin kullanılacağı dalga yapıcı ve rüzgar nozülü, tezde de küçük bir açıklama olarak verilmiştir.
Yüzer Rüzgar Türbinleri Araştırması için Bir Yatay Rüzgar Türbininin Ölçeklendirilmiş Modellemesi
Thesis (Master)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2020
Includes bibliographical references (leaves: 72-75)
Text in English; Abstract: Turkish and English
Keywords: Flow analysis; Wind turbines; Experimental desing; Blade desing